Klekluk! - Garcellano, Lemuel (Chikiting books, 2013)
"These past few days, Arbi often comes home with bumps and bruises. He says he had a fight with three headed insects, the kleklukS... This book gives life to the touching story of a son's great love for his mother, and the lesson it brings about having courage to accept things one cannot change."